Fiber-Optic Vector Magnetic Field Sensor Based on Mode Interference and Magnetic Fluid in a Two-Channel Tapered Structure - He Tian; Yuxiao Song; Yanzeng Li; Hanyang Li (IEEE Photonics Journal)
An innovative approach to high-sensitivity simultaneous intensity and direction measurement in a two-channel tapered sensor is proposed and demonstrated. The sensor is comprised of magnetic fluid (MF)- filled micro-capillary and two accompanying micro-fiber, thus enabling evanescent interaction to take place between the optical mode in the capillary and MF. Given the magnetic nanoparticles (MNPs) of MF manifest anisotropic magnetic field. Experimental and numerical simulations were performed simultaneously, which provided a better understanding of the interaction between light and MF in addition to clarifying the dynamic process of MNPs within MF with the assistance of varying magnetic field. The experimental results are well consistent with the numerical simulation results and show that the sensitivity of this sensor reaches up to 244 pm/mT, with the direction error being merely ±1.4°. Therefore, the proposed sensor exhibits a unique sensitivity for the measurement of magnetic field intensity and direction in 3D space, which makes it best suitable for applications in transportation, medicine, and smart device.